2019
DOI: 10.1002/pro6.1074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rotary cell culture system‐simulated microgravity on the ultrastructure and biological behavior of human MDA‐MB‐231 breast cancer cells

Abstract: Objective: This study aimed to investigate changes in the ultrastructure, apoptosis, cycle progression, and migration ability of human MDA-MB-231 breast cancer cells under simulated microgravity conditions. Methods: MDA-MB-231 breast cancer cells were cultured in a rotary cell culture system bioreactor to simulate microgravity for 7 days. The cells were randomly divided into a simulated microgravity (SMG) group and normal gravity control (NG) group. Changes in apoptosis, ultrastructure, cell cycle, and migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…It is designed as a bioreactor system to simultaneously incorporate the ability to culture multiple types of cells with low turbulence and high mass transfer of nutrients. Jiang et al, (2019) investigated human MDA-MB-231 breast cancer cells in the RCCS to examine microgravity on the ultrastructure [31]. They aimed to determine the changes in the apoptosis, ultrastructure, and cycle progression for seven days.…”
Section: Rotary Cell Culture Systemmentioning
confidence: 99%
“…It is designed as a bioreactor system to simultaneously incorporate the ability to culture multiple types of cells with low turbulence and high mass transfer of nutrients. Jiang et al, (2019) investigated human MDA-MB-231 breast cancer cells in the RCCS to examine microgravity on the ultrastructure [31]. They aimed to determine the changes in the apoptosis, ultrastructure, and cycle progression for seven days.…”
Section: Rotary Cell Culture Systemmentioning
confidence: 99%
“…Cancer cell death has often been attributed to a dysfunctional cytoskeleton or cell cycle arrest caused by microgravity [ 160 , 161 , 162 ]. In addition, abnormal expression of apoptosis-related proteins (p53, Fas, Bax, p21, and Bcl-2) and tumor suppressor genes ( TP53 , PTEN , and FOXO3 ) has been found in cancer cells that showed increased apoptosis [ 6 , 124 , 151 , 152 , 161 , 163 , 164 ].…”
Section: Impact Of Microgravity On Apoptosis In Different Cell Typmentioning
confidence: 99%
“…This could explain the different starting points of apoptosis in microgravity cultures: In ML-1 and ONCO-DG1 thyroid cancer cells, apoptosis increased after 24 h exposure to simulated microgravity [ 6 , 140 ], whereas in MDA-MB-231 breast cancer and SGC-7901 gastric adenocarcinoma cells, apoptosis increased only after 72 h [ 149 , 152 ]. On the other hand, the number of secondary lysosomes also increased in MDA-MB-231 cells cultured in a RCCS [ 160 ]. A possible role of miRNA expression in the regulation of autophagy-related apoptosis in microgravity needs to be investigated in future studies [ 172 ].…”
Section: Impact Of Microgravity On Apoptosis In Different Cell Typmentioning
confidence: 99%
“…This way, it can counteract the pro-apoptotic stress occurring during tumorigenesis. Recently, Jiang et al [ 86 ] described that apoptosis of MDA-MB-231 cells was promoted by RCCS culture (7 days) by decreased expression of the anti-apoptotic Bcl-2 as well as increased expression of the pro-apoptotic Fas protein, further accompanied by the appearance of a large number of lysosomal and vacuolar structures.…”
Section: Breast Cancer Cells Exposed To Microgravitymentioning
confidence: 99%
“…For MCF-7 cells, Qian et al [ 78 ] found that the invasive ability decreased after clinostat exposure together with a reduced expression of matrix-metallopeptidases (MMP-2, MMP-9) and vinculin. A transwell migration assay showed that the migration of MDA-MB-231 cells was also significantly reduced after 72 h on an RCCS [ 86 ]. The authors concluded that the decrease in MMP-9 expression in MDA-MB-231 cells might be closely related to a decrease in migration ability in s-µ g .…”
Section: Breast Cancer Cells Exposed To Microgravitymentioning
confidence: 99%